2005
DOI: 10.1007/s10633-005-7554-3
|View full text |Cite
|
Sign up to set email alerts
|

Regional Assessment of Cone System Function Following Uncomplicated Retinal Detachment Surgery

Abstract: Central and paracentral cone system dysfunction may be detected even at lengthy time intervals from retinal reattachment, independent of the presence of a pre-operative macular RD. The extent of central loss appears to be inversely related to RD duration, in agreement with previous reflectometric findings on foveal cone photopigment density [Liem et al., 1994; Ophthalmology 10: 1945-51].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…Previous studies have suggested that retinal detachment may have different magnitudes of effect on the scotopic versus photopic ERG responses. [ 14 15 ] However, in this study, we did not observe a difference in the magnitude of dysfunction between the rod- and cone-driven pathways, suggesting that both subsets of photoreceptors are similarly affected.…”
Section: Discussioncontrasting
confidence: 59%
“…Previous studies have suggested that retinal detachment may have different magnitudes of effect on the scotopic versus photopic ERG responses. [ 14 15 ] However, in this study, we did not observe a difference in the magnitude of dysfunction between the rod- and cone-driven pathways, suggesting that both subsets of photoreceptors are similarly affected.…”
Section: Discussioncontrasting
confidence: 59%
“…Cone system dysfunction may still be detected even long intervals after retinal reattachment, independent of the presence of a preoperative macular RD [23]. It also has been shown that there is a significant correlation between outer nuclear layer (ONL) cell count and flicker ERG amplitude in the reattached retina [24].…”
Section: Discussionmentioning
confidence: 99%
“…Although we could not assess cone functionality using electrophysiology, this deserves further explorations. Indeed, previous electrophysiological studies of RD human eyes have reported reduced amplitudes and increased latencies compared to normal values, in full filed electroretinograms (ERGs) [31], focal ERGs [32] or multifocal ERGs [33], with evidence for retinal dysfunction due to outer retinal alterations in primary macula-off RD.…”
Section: Discussionmentioning
confidence: 99%